A case of metastatic cancer Zapallal late Middle Horizon (1100-1200 AD), Chillon Valley, Peru - Altamirano Enciso, Alfredo Jose (2013)
The found of a male human burial 35-40 years old of archaeological site of Zapallal, Puente Piedra, North of Lima, showing malignant tumor, has permitted study the old theme of neoplasmas or cancers in Andean world. This article shows the differential diagnosis and its discussions about their possibly causes to the light of paleopathology focus. It describes the severe destructive lesions in bones of pelvis and sacro, concluding in prostate cancer cause